Pengaruh Naungan Terhadap Ekspresi Gen PEPC dan Rubisco Serta Kerapatan Stomata dan Kadar Klorofil pada Tanaman Tebu (Saccharum officinarum L.) - Venus Artha Ramadhanni (Fakultas Pertanian, 2026)
The Effect Of Shading On PECP And Rubisco Gene Expression, Stomatal Density, And Chlorophyll Content In Sugarcane (Saccharum officinarum L.); Venus Artha Ramadhanni, 221510501006, Agrotechnology Study Program, Faculty Of Agriculture, University Of Jember. This study aimed to determine the effect of shading on the expression of PEPC and Rubisco genes, stomatal density, and chlorophyll content in sugarcane (Saccharum officinarum L.). The experiment was conducted using three shading treatments, namely no shading (0%) as control, 20% shading, and 40% shading. The observed parameters included plant height, chlorophyll content, total stomatal density, and the expression levels of PEPC and Rubisco genes. The collected data were statistically analyzed to evaluate the effects of shading treatments on the observed variables. The results showed that sugarcane plants grown without shading exhibited normal and optimal plant growth, chlorophyll content, stomatal density, and PEPC and Rubisco gene expression. In contrast, increasing shading levels led to reductions in plant height, chlorophyll content, and stomatal density, along with alterations in PEPC and Rubisco gene expression. These results indicate that shading induced stress conditions in sugarcane plants due to reduced light intensity. It can be concluded that shading significantly affects physiological characteristics, leaf anatomical traits, and the expression of photosynthesis- related genes in sugarcane. Keywords: shading, sugarcane, PEPC, Rubisco, chlorophyll, stomatal density
Finalisasi 24 Juni 2026_Yudi
Keywords: Shading; Sugarcane; PEPC; Rubisco; Chlorophyll; Stomatal Density